Antibiogram of Urinary Isolates in Chattogram - Mokarrama, Moniat; Sultana, Kawsar; Salsabil, Sabira (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Despite the widespread availability of antibiotics, Urinary Tract Infection (UTI) is one of the most important causes of morbidity in general population and also the common cause of nosocomial infection among hospitalized patients. This is due to resistance of antibiotics and the ever changing pattern of the sensitivity. The purpose of the study was to identify the recent pattern of antibiogram and sensitivity and to help physician in prescribing empirical therapy against the newest sensitivity pattern. Materials and methods: This cross-sectional study was carried out in the Department of Microbiology of Chattagram Maa Shishu-O-General Hospital, National Hospital Chattogram and Max Hospital Laboratory, Chattogram from February to July 2022. Sample size was 100 positive urine culture reports from each lab. Results: The male to female ratio of the patients was 1:2.22. Escherichia coli was the dominant isolate (53%) followed by Klebsiella spp. (19%), Enterococcus spp. (16%), both Coagulase negative Staphylococcus and Pseudomona (5%) and Proteus (2%). The three most frequently isolated bacteria had resistance rates of 100% to Penicillin and sensitivity rates of 20-89% to Amikacin,67%-100% to Tigecycline, 42%- 88% to Nitrofurantoin and 80%- 89% to Meropenam. E.coli and Klebsiella also had resistance rates of 69%- 94% to Cefixime and 83%-88% to Cefuroxime. Conclusion: In the study area resistance rates to Penicillin, Cefixime and Cefuroxime were high. Since most isolates were sensitive to Tigecycline, Nitrofurantoin and Meropenam, they are considered as appropriate antimicrobials for empirical treatment urinary tract infections. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 72-76